Explicit, Express, and Everything in Between: The Quid Pro Quo Requirement for Bribery and Hobbs Act Prosecutions in the 2000s - Ilissa B. Gold (Washington University Journal of Law & Policy, 2011)
The Article focuses on quid pro quo requirement for bribery under the U.S. Hobbs Act of 1946. Information is provided on how the law aimed to curtail labor racketeering, bribery, and extortion affecting interstate commerce but evolved to include the acceptance of bribes by public officials. The author discusses the need for a quid pro quo requirement for conviction under the Act.
Keywords: Bribery; Racketeering; Commercial law; Interstate commerce -- Law & legislation; Organized crime